Predicting the Effects of Perceived Service Quality and Logistics Service Innovation on Repurchase Intention of Instant Courier Services through Customer Satisfaction and Trust - Kunthi A. Kusumawardani; Saras Asa Hastayanti (Jurnal Manajemen Indonesia, 2020)
Logistics are not only playing a significant role in the business process, but they can also add value to the business, and even also determine the life of the firm. Due to its significance, the advancement of logistics is inevitable. Customers want everything faster, and they are even willing to pay more for the service. This study provides an empirical investigation of instant courier service customers in Indonesia. A total of 300 valid questionnaires were collected and assessed using structural equation modelling (SEM). The results showed that perceived service quality influences customer satisfaction and trust. On the other hand, logistics service innovation influences perceived service quality but not customer satisfaction. While trust affects customer satisfaction and repurchase intention. Moreover, customer satisfaction influences repurchase intention. This study is one of the first to evaluate and confirm the relations of service quality-repurchase intention in instant courier service. This research contributes to the literature for future research in instant courier service by providing empirical evidence in Indonesia. Keywords— Customer Satisfaction; Logistics Service Innovation; Perceived Service Quality; Repurchase Intention; Trust